THE EFFECT OF SAFETY AND HEALTH APPLICATION ON EMPLOYEES’ ACHIEVEMENT THROUGH WORK SATISFACTION AS INTERVENING VARIABLES IN AMUNITION FACTORY - Firdausi, Faidhotur Rohmah; Mu'is, Ahmad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Competition in the fight for the market from all the lines of regional, national, and international continues to be done by every company on a competitive basis. To reach a company that is ready to compete, of course, will not be separated from human resources which is the determinant of success in running the vision of the mission and in achieving the target, so the corporation will give occupational safety and health facilities in employees to improve work performance. The purpose of this study is to determine the influence direct occupational safety and health to the work performance of employees and to determine the indirect effect of occupational safety and health on employee performance through job satisfaction. Population in this research is all employees of Department of Device Division of Pindad Corporation in Turen Malang and sampling technique is a sample saturated with a sample of 45 employees. Testing hypothesis research using path analysis technique with SPSS application. The result of research indicate that there is no influence directly or indirectly between work safety variable and job satisfaction to work performance. For job satisfaction variable, the value of coefficient of beta influence of job satisfaction on job performance. Then the magnitude of the direct effect of occupational health to work performance of 0.481. While indirect influence of occupational health to work performance through job satisfaction obtained beta coefficient value 0,595 with sig. 0,000. Because sig. 0.000 <0,05 hence occupational health effect to job satisfaction. But the path of job satisfaction on work performance does not affect. It can be concluded that there is no direct or indirect influence between work safety and occupational health on job performance through job satisfaction.